A geometrical approach for the measurement of the volume of masses of granular material through grid-layout sensor networks. (February 2020) - Bocci, Cristiano; Fort, Ada; Pozzebon, Alessandro; Bertoni, Duccio
Highlights: Volume of masses of granular material is computed by means of geometrical approach. Measurement is performed through grid-layout sensor networks. Possible wired and wireless sensor network architectures are presented. Accuracy of the method is lower than 1% according to the sensor frequency. The proposed geometrical approach can be computed on resource-constrained devices. Abstract: In this paper, the authors propose a novel methodology to measure the volume of masses of granular material by means of wired or wireless sensor networks. The proposed technological framework exploits a grid of sensor nodes, each of them in charge of measuring the level of a layer of granular material in a specific point. Since this layout allows to subdivide an area in grid of squares, 4 sensor nodes are expected to sit at the corners of each square, where they will be able to punctually measure the level of the layer. This paper proposes a geometrical approach to calculate the volume of the material in the area covered by the sensors using these data sets. Thanks to the proposed calculation methodology, the volume can be estimated by means of simple geometrical calculations that can be easily performed on a resource-constrained device like a microcontroller.